The impact of material thought on scientific deviation and intellectual conflict - Hammouda, Abed El Fatah Fathi (Social Empowerment Journal, 2022)
This research aims to highlight the impact of materialistic thought in the deviation of the March of Science and in the intellectual conflict in Western societies, where the spread of materialistic thought in the modern era was clearly reflected on Western societies, and then on Arab and Islamic societies, and this had serious and bad effects, especially in the intellectual and ideological level, and these intellectual effects: "The impact of material Thought on scientific deviation and intellectual conflict", which consists of an introduction and researchers. the first research talked about the impact of material Thought on scientific deviation, such as the monopoly of absolute truths, the link between scientific progress and material thought, and the connection of material thought with the experimental method. the second research talked about the effects of material thought in the Western intellectual conflict, such as the establishment of material Thought on the philosophical method, the relationship of materialism with different philosophies, such as idealism, spirituality, and rationalism